Rare Cases of Bronchial Aneurysm and Comparison of Interventional Embolization in the Treatment of True Bronchial Aneurysm and Pseudobronchial Aneurysm - Lin, Jia-Li; Ji, Yuan-Yuan; Zhang, Ming-Zhe; Tang, Yi; Wang, Ruo-Li; Ruan, Dan-Dan; Zhou, Yan-Feng; Wu, Shao-Jie; Cai, Sen-Lin; Zhang, Jian-Hui; Meng, Xiao-Rong; Luo, Jie-Wei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Bronchial artery aneurysm(BAA) is a rare disease. Rupture of BAA can lead to life-threatening hemoptysis, and once diagnosed, treatment is needed regardless of symptoms. Transcatheter artery embolization is the first choice of treatment because it is minimally invasive and effective. This study aimed to retrospectively compare the embolization treatment of a case of true BAA and that of a pseudobronchial aneurysm and explore the choice of embolization method for BAA with short neck or no neck. Materials and methods: Embolization treatment and imaging characteristics of one case of true BAA and one case of pseudobronchial aneurysm admitted to our hospital were analyzed retrospectively. Embolization methods and therapeutic effects of two cases of BAAs were compared. Results: Case 1 was that of an intact true BAA inside the mediastinum located at the opening of the bronchial artery. The distal end of the aneurysm was embolized, and tumor cavity was occluded. No recurrence of BAA was found after the operation. Case 2 was that of a ruptured and hemorrhagic pseudobronchial aneurysm of the mediastinum. Coil embolization combined with covered stent graft exclusion of the thoracic aorta were performed, and the left bronchial artery and BAA were almost occluded. Nine months postoperatively, the mediastinal hematoma was almost completely absorbed. Conclusion: Endovascular embolization has become the most commonly used for the treatment of BAA. Different methods should be selected according to the location and nature of the aneurysm.